Actualization of Digital Marketing Society 5.0 on MSMES of Sasirangan Cloth in Village Sasirangan in Banjarmasin City - Tino Kemal Fattah; Putriana Salman (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2021)
Marketing is part of the main activities carried out by traders in their efforts to maintain the survival of their business to achieve business goals. Strategy is a process of determining an organizational goal, accompanied by the preparation of a way or effort how to achieve that goal. In particular, strategy is an action that is increasing and continuous and is done based on the point of view of what customers expect in the future. This research aims to find out how the actualization of digital marketing of MSMEs in the era of society 5.0. This research method uses quantitative descriptive methods with data collection techniques through questionnaire sharing. The population in this study is MSMEs Kain Sasirangan in Kampung Sasirangan Banjarmasin City. The results of this study show that Sasirangan MSMEs have used digital marketing in the process of buying and selling their products. It is recognized that the utilization of digital marketing can expand market reach and add new customers, facilitate business management with more flexible time, can be done at any time without having to open a store first, so that the profits obtained are also greater. In addition, by utilizing digital marketing, MSME sasirangan fabric actors do not need a place to sell their products, so the costs incurred are also less. Their lack of ability to use technology, only able to make them do marketing their products traditionally.